Highly dispersed Pt nanoparticles confined within hierarchical pores of silicalite-1 zeolite via crystal transformation of supported Pt/S-1 catalyst for partial oxidation of methane to syngas. (13th August 2019) - Ma, Lichao; Ding, Chuanmin; Wang, Junwen; Li, Yufeng; Xue, Yanan; Guo, Jing; Zhang, Kan; Liu, Ping; Gao, Xiaofeng
Abstract: Highly dispersed Pt nanoparticles confined within hierarchical pores of silicalite-1 zeolite were prepared via crystal transformation of supported Pt/S-1 catalyst. Selective dissolution and external recrystallization in tetrapropylammonium hydroxide solution enabled metal nanoparticles to be encapsulated in zeolites. The abundant pore structures of as-prepared Pt@S-1 catalyst were obtained by properly controlling the time of desilication and recrystallization. The properties of Pt@S-1 catalyst with hierarchical pores were characterized by XRD, ICP, SEM, TEM/HRTEM, N2 /Ar adsorption-desorption, CO adsorption, H2 -TPR and TGA techniques. Compared with the traditional supported Pt/S-1 catalyst, Pt@S-1 catalyst exhibited excellent sintering resistance, owing to the restriction of the recrystallized shell. Further, abundant pore provided access to contact with the active components, the Pt@S-1 catalyst showed excellently catalytic performance. CH4 conversion and product selectivity were significantly improved. The out-standing catalytic performance was attributed to recrystallization of silica supported Pt. The strategy afforded enriched pore structure, improved the dispersion of active metal, and reduced the size of Pt nanoparticles. In addition, hierarchical pores of silicalite-1 zeolite supports also contributed to shorten the diffusion path of reactions. Highlights: The Pt@S-1 catalyst with hierarchical pores zeolite shell were synthesized. Highly dispersed Pt nanoparticles confined within hierarchical pores zeolite. The confinement improved anti-sintering of Pt catalyst. The shortened diffusion path of reactions enhanced the catalytic activity.